Comparison of high flow oxygen therapy versus noninvasive mechanical ventilation for successful weaning from invasive ventilation in children: An observational study. Issue 39 (30th September 2022) - Celik, Nur Berna; Tanyildiz, Murat; Yetimakman, Filiz; Kesici, Selman; Bayrakci, Benan
Abstract : Post-extubation respiratory failure is associated with a poor prognosis due to increased ventilator-associated pneumonia, and longer length of stay in the ICU and hospital. In this study, we aimed to evaluate the efficacy of high-flow nasal cannula (HFNC) and noninvasive mechanical ventilation (NIMV) on extubation success in children. A total of 48 patients, aged between 1 month and 18 years, who were weaned to either NIMV or HFNC were included. Patients who had tracheostomy or were not weaned and underwent unplanned extubation were excluded. Age, gender, anthropometric parameters, Pediatric Risk of Mortality and Pediatric Logistic Organ Dysfunction scores, oxygenation index, mechanical ventilation length of stay (LOS), HFNC/NIMV LOS, Modified Downes-Silverman score (MDS), and venous blood gas parameters, pediatric intensive care unit (PICU) LOS were recorded. 24 patients were extubated to NIMV, and 24 patients to HFNC. HFNC LOS and NIMV LOS were similar ( P  = .621). The failure rates at the 48th hour of HFNC and NIMV were 33% (n = 8), and 33% respectively (n = 8) ( P  = 1.0). PICU LOS and mortality rate was also similar ( P  = .06, P  = .312 respectively). MDS decreased significantly in both groups ( P  < .001, P  = .02 respectively). Changes in blood gas parameters and MDS within the first 48-hour of device application were similar between the 2 groups. HFNC is not inferior to NIMV in patients with extubation difficulty or those expected to have such difficulty in terms of treatment success, PICU LOS, and mortality. Therefore, HFNC appears to be a weaning technique alternative to NIMV after extubation.